Poly-ICLC, a TLR3 Agonist, Induces Transient Innate Immune Responses in Patients With Treated HIV-Infection: A Randomized Double-Blinded Placebo Controlled Trial - Saxena, Mansi; Sabado, Rachel L.; La Mar, Melissa; Mohri, Hiroshi; Salazar, Andres M.; Dong, Hanqing; Correa Da Rosa, Joel; Markowitz, Martin; Bhardwaj, Nina; Miller, Elizabeth (Frontiers in Immunology, 2019)
Objective: Toll-like receptor-3 agonist Poly-ICLC has been known to activate immune cells and induce HIV replication in pre-clinical experiments. In this study we investigated if Poly-ICLC could be used for disrupting HIV latency while simultaneously enhancing innate immune responses. Design: This was a randomized, placebo-controlled, double-blinded trial in aviremic, cART-treated HIV-infected subjects. Participants (n=15) were randomized 3:1 to receive two consecutive daily doses of Poly-ICLC (1.4mg subcutaneously) versus placebo. Subjects were observed for adverse events, immune activation and viral replication. Methods: Besides primary outcomes of safety and tolerability, several longitudinal immune parameters were evaluated including immune cell phenotype and function via flowcytometry, ELISA and transcriptional profiling. PCR assays for plasma HIV-1 RNA, CD4+ T cell-associated HIV-1 RNA and proviral DNA were performed to measure HIV reservoirs and latency. Results: Poly-ICLC was overall safe and well-tolerated. Poly-ICLC-related adverse events were Grade 1/2, with the exception of one Grade 3 neutropenia which was short-lived. Mild Injection site reactions were observed in nearly all participants in the Poly-ICLC arm. Transcriptional analyses revealed upregulation of innate immune pathways in PBMCs following Poly-ICLC treatment, including strong interferon signaling accompanied by transient increases in circulating IP-10 (CXCL10) levels. These responses generally peaked by 24-48 hours after the first injection and returned to baseline by day 8. CD4+ T cell number and phenotype were unchanged, plasma viral control was maintained and no significant effect on HIV reservoirs was observed. Conclusions: These finding suggest that Poly-ICLC could be safely used for inducing transient innate immune responses in treated HIV+ subjects indicating promise as an adjuvant for HIV therapeutic vaccines. Trial Registration: ClinicalTrials.gov identifier: NCT02071095.